Help onto the housing ladder: The role of intergenerational transfers - Bee Boileau; David Sturrock (Institute for Fiscal Studies (IFS), 2023)
This report describes patterns of financial help from family received by first-time buyers. We quantify the value of gifts and loans made, how they vary across different regions of the country and between those from different parental backgrounds, and shed light on their role in explaining inequalities in homeownership and wealth.
Keywords: 330; Poverty; inequality and social mobility; Savings; pensions and wealth; Family; Housing; Inequality; Savings; Social mobility; Wealth